The Diagnostic Value of Thrombopoietin Level Measurements in Thrombocytopenia - Porcelijn, Leendert; Folman, Claudia C.; Bossers, Bernadette; Huiskes, Elly; Overbeeke, Marijke A. M.; Schoot, C. Ellen v. d.; de Haas, Masja; Borne, Albert E. G. Kr. v. d. (Thrombosis and Haemostasis, 1998)
It has been reported that blood trombopoietin (TPO) levels can discriminate between thrombocytopenia due to increased platelet destruction and decreased platelet production. With our TPO ELISA and a glycocalicin ELISA we analysed a large group of patients in detail and could confirm and amplify the above notion in detail.TPO levels were determined in plasma from 178 clinically and serologically well-defined thrombocytopenic patients: 72 patients with idiopathic autoimmune thrombocytopenia (AITP), 29 patients with secondary AITP, 5 patients with amegakaryocytic thrombocytopenia and 72 patients who suffered from various diseases (46 in whom megakaryocyte deficiency was not and 26 in whom it was expected). In addition, we measured the level of glycocalicin as a marker of total body mass of platelets.In all patients with primary AITP and secondary AITP, TPO levels were within the normal range or in some (n = 7) cases only slightly increased. The level of glycocalicin was not significantly different from that of the controls (n = 95). The patients with amegakaryocytic thrombocytopenia had strongly elevated TPO levels and significantly decreased glycocalicin levels. Similarly, among the 72 thrombocytopenic patients with various disorders, elevated TPO levels were only found in patients in whom platelet production was depressed. The mean level of glycocalicin in these patients was decreased compared to that in controls and patients with AITP, but was not as low as in patients with amegakaryocytic thrombocytopenia.In conclusion, all patients with depressed platelet production had elevated levels of circulating TPO, whereas the TPO levels in patients with an immune-mediated thrombocytopenia were mostly within the normal range. Therefore, measurement of plasma TPO levels provides valuable diagnostic information for the analysis of thrombocytopenia in general.Moreover, treatment with TPO may be an option in AITP.